Experimental and numerical investigation of Poole–Frenkel effect on dynamic RON transients in C-doped p-GaN HEMTs. (20th December 2021) - Zagni, Nicolò; Cioni, Marcello; Iucolano, Ferdinando; Moschetti, Maurizio; Verzellesi, Giovanni; Chini, Alessandro
Abstract: In this paper, we investigate the influence of Poole–Frenkel effect (PFE) on the dynamic R ON transients in C-doped p-GaN HEMTs. To this aim, we perform a characterization of the dynamic R ON transients acquired during OFF-state stress (i.e. V GS, STR = 0 V < V T, V DS, STR = 25–125 V) and we interpret the results with the aid of numerical simulations. We find that dynamic R ON transients at room temperature accelerate with V DS, STR 1/2, which is signature of PFE, as further confirmed by the simultaneous decrease of the activation energy ( E A ) extracted from the Arrhenius plot of the dynamic R ON transients at V DS, STR = 50 V and T = 30 °C–110 °C. Results obtained by means of calibrated numerical simulations reproduce the exponential dependence of transients time constants ( τ ) on V DS, STR 1/2 and consequent E A reduction only when including the PFE-enhancement model of hole emission from dominant acceptor traps in the buffer related to C doping. This result is consistent with the 'hole-redistribution' model that considers hole emission from acceptor traps (rather than electron capture) as the mechanism underlying dynamic R ON increase during OFF-state stress.